Enhancing Student Learning Outcomes in Social Studies: An Investigation Into The Lazarus Educational Game - Burhan; Runniarsiti; Arsyad, Susalti Nur; Putri, Fina Melani; Malik, Agung Rinaldy (Universitas Pendidikan Ganesha, 2024)
The rapid advancement of technology gives the opportunity to incorporate digital games and other technology-driven tools into the IPS curriculum. This study aimed to analyze the influence of the Lazarus educational game on enhancing social and cognitive learning outcomes in the subject of Social Studies elementary school. A quantitative experimental approach was employed, with a sample of 53 fourth-grade students divided into two groups: an experimental group (IV-B) and a control group (IV-A). Data were collected through tests, interviews, and documentation, and analysed using simple linear regression and t-test. The research findings revealed a positive impact of the Lazarus educational game on students' social development, indicating an improvement in student engagement and social interactions. Additionally, a significant difference in cognitive learning outcomes was observed between two groups. The experimental group (IV-B) exhibited higher learning outcomes compared to the control group (IV-A), underscoring the effectiveness of the Lazarus game as a learning tool. This study makes a valuable contribution to the advancement of teaching methods, particularly in the context of the IPS subject. The use of the Lazarus educational game serves as an effective alternative for enhancing student learning outcomes, particularly in their social development. Practical implications of this research suggest that educators can consider incorporating the Lazarus educational game as a teaching strategy to improve classroom learning, particularly in the field of IPS.